PENGEMBANGAN BAHAN AJAR BERBASIS AKTIVITAS DENGAN MEDIA CD INTERAKTIF PADA MATERI INDERA PENDENGARAN DAN SISTEM SONAR - Arni Nurmariza; Muslimin Ibrahim; Wahono Widodo (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research aims to develop the activities-based instructional material in junior high school natural science learning on sense of hearing and sonar systems topic through Media Interactive CD to improve learning achievement. This research use research and development. The model used is taken from Dick and Careys developmental model. The tests used are one group pre-test and post-test. The data analysis technique used descriptive quantitative and qualitative. The results showed that (1) the validation of teaching materials id categorized as feasible, (2) the feasibility of teaching materials with the average score of 3.7 is categorized as good, the percentages of students' response to learning and media are 98.81% and 90.48% , categorized as very good, 99,29% legibility of media is categorized as very good, (3) the effective teaching materials to reach the achievement of students competency and activate students gets an average score of 3.25, the cognitive aspect of learning outcomes is categorized as "B+", the aspect of skill is 3.58, categorized as " A- ", aspects of spiritual attitude is 3.67, categorized as very good, aspects of social attitudes is 3.60, categorized as very good. Based on the research findings, we can conclude that the activities-based instructional material in junior high school natural science learning on sense of hearing and sonar systems topic through Media Interactive CD is feasible, practical and effective to be used in the teaching and learning process.  Penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis aktivitas dengan media CD interaktif dalam pembelajaran IPA SMP pada materi indera pendengaran dan sistem sonar untuk meningkatkan hasil belajar siswa. Jenis penelitian ini merupakan penelitian pengembangan bahan ajar. Model pengembangan yang  digunakan  adalah  model  Dick  and  Carey.  Uji  coba  bahan  ajar  di  dalam  kelas  menggunakan rancangan one group pre-test and post-test design. Teknik analisis yang dikembangkan adalah deskriptif kuantitaif dan kualitatif. Hasil penelitian menunjukkan bahwa (1) validasi bahan ajar berkategori layak, (2) kepraktisan bahan ajar berkategori baik dengan skor rata-rata keterlaksanaan 3,7 berkategori baik, persentase respon siswa terhadap pembelajaran dan media 98,81% dan 90,48% berkategori sangat baik, keterbacaan media 99,29% berkategori sangat baik, (3)  bahan  ajar  efektif untuk menfasilitasi siswa mencapai ketercapaian kompetensi dan mengaktifkan siswa dengan skor rata-rata hasil belajar aspek pengetahuan 3,25 berkategori œB+, aspek keterampilan 3,58 berkategori œA-œ, aspek sikap spiritual 3,67 berkategori sangat  baik,  aspek  sikap  sosial  3,60  berkategori  sangat  baik.  Berdasarkan temuan  hasil penelitian dapat disimpulkan bahan ajar berbasis aktivitas dengan media CD interaktif dalam pembelajaran IPA SMP pada materi indera pendengaran dan sistem sonar layak, praktis dan efektif digunakan dalam proses pembelajaran.